Molecular Characterization Based on MLST and ECDC Typing Schemes and Antibiotic Resistance Analyses of Treponema pallidum subsp. pallidum in Xiamen, China - Liu, Dan; He, Shu-Min; Zhu, Xiao-Zhen; Liu, Li-Li; Lin, Li-Rong; Niu, Jian-Jun; Yang, Tian-Ci (Frontiers in Cellular and Infection Microbiology, 2021)
In total, forty nine clinical samples were analyzed using two typing schemes, ECDC and MLST, to describe the molecular characteristics of circulating T. pallidum isolates in Xiamen between 2016 and 2017. In addition, genetic mutations potentially related to antibiotic resistance of T. pallidum were also analyzed. Forty five samples were fully typed by ECDC, and fourteen different subtypes were detected. The most common subtype was 16d/f (24.4%), followed by 14d/f (20.0%). All forty nine samples were successfully typed by MLST, while only four allelic profiles were identified, including three SS14-like profiles and one Nichols-like profile. Among them, the major allelic profile was 1.1.8 (85.7%). Interestingly, the allelic profile 1.3.1 widespread in Europe and North America was not detected in this region. Additionally, A2058G mutation in 23S rRNA was found in all detectable samples (38/38), and no mutation in 16S rRNA was observed (36/36). Four nonsynonymous single-nucleotide polymorphisms in penicillin-binding protein genes were found in the thirty-five samples eligible for Sanger sequencing. Among them, the variant in tp0500 (P564I) can only be found in the SS14-like isolates. Homoplastic changes in tp0760 (I415F/I415M) and tp0705 (A506V/A506T) were found. Moreover, the variant tp0705 A506V and the variant tp0705 A506T separately appeared in the SS14-like isolates and Nichols-like isolates, respectively. This study showed that the genotypes of T. pallidum isolates in Xiamen between 2016 and 2017 were different from those in other geographic areas. The resistance-related variants of T. pallidum isolates identified in this study could provide awareness for clinicians in the treatment of syphilis.